Shakespearean metaphysics - Witmore, Michael (Shakespeare now!, 2008)
This new approach to Shakespeare's plays suggests they can be seen as metaphysical 'experiments' conducted in the medium of drama. It engages readers with lively discussion of three 'difficult' metaphysical thinkers - Spinoza, Bergson and Whitehead - through 'The Tempest', 'King Lear' and 'Twelfth Night'.